Architecture : A Very Short Introduction - Ballantyne, Andrew (Karachi, Pakistan Oxford University Press, 2006)
This guide intends to help us understand the cultural significance of the buildings that surround us. It avoids the traditional style-spotting approach in favour of giving an idea of what it is about buildings that moves us.
Include Index, Glossary and Colour Illustration
Keywords: Architecture -- Bouwkunst